Carboxyl-terminated butadiene-acrylonitrile-toughened epoxy/carboxyl-modified carbon nanotube nanocomposites: Thermal and mechanical properties - H. F. Xie; Y. T. Wang; C. S. Wang; H. Y. Yin; L. L. Wang; R. S. Cheng (eXPRESS Polymer Letters)
Carboxyl-modified multi-walled carbon nanotubes (MWCNT–COOHs) as nanofillers were incorporated into diglycidyl ether of bisphenol A (DGEBA) toughened with carboxyl-terminated butadiene-acrylonitrile (CTBN). The carboxyl functional carbon nanotubes were characterized by Fourier-transform infrared spectroscopy and thermogravimetric analysis. Furthermore, cure kinetics, glass transition temperature (Tg), mechanical properties, thermal stability and morphology of DGEBA/CTBN/MWCNT–COOHs nanocomposites were investigated by differential scanning calorimetry (DSC), dynamic mechanical analysis (DMA), universal test machine, thermogravimetric analysis and scanning electron microscopy (SEM). DSC kinetic studies showed that the addition of MWCNT–COOHs accelerated the curing reaction of the rubber-toughened epoxy resin. DMA results revealed that Tg of rubber-toughened epoxy nanocomposites lowered with MWCNT–COOH contents. The tensile strength, elongation at break, flexural strength and flexural modulus of DGEBA/CTBN/MWCNT-COOHs nanocomposites were increased at lower MWCNT-COOH concentration. A homogenous dispersion of nanocomposites at lower MWCNT–COOH concentration was observed by SEM.